(2*x+1)*(2*x+2)*(2*x+3)
Răspunsuri la întrebare
Răspuns de
1
(2x+1)*(2x+2)*(2x+3)=(2x*2x+4x+2x+2)*(2x+3)=(4x^2+6x+2)*(2x+3)=8x^3+12x^2+4x+12x^2+18x+6=8x^3+24x^2+22x+6
RASPUNS FINAL:8x^3+24x^2+22x+6
Răspuns de
1
(2x+1)*(2x+2)*(2x+3)=(2x*2x+4x+2x+2)*(2x+3)=(4x^2+6x+2)*(2x+3)=8x^3+12x^2+4x+12x^2+18x+6=8x^3+24x^2+22x+6
Succes!!シ︎
Alte întrebări interesante
Franceza,
8 ani în urmă
Chimie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă